Penguasaan Bapak Terhadap Hak Asuh Anak di Bawah Umur Setelah Perceraian di Kabupaten Padang Lawas - Sainul, Ahmad Sainul (LP2M IAIN Palopo, 2025)
This article is intended to examine the control of child custody rights by fathers after divorce in Padang Lawas Regency. Field studies using juridical-empirical as the approach. The primary data source of this study is the results of interviews with husbands and wives who exercise child custody rights after divorce and traditional leaders of Padang Lawas Regency. Secondary data sources are in the form of the Compilation of Islamic Law, Law Number 1 of 1974 concerning Marriage, books, journals, and other materials relevant to this study. This study was analyzed using a descriptive approach. The results of the study show that child custody rights are fully the rights of fathers after divorce in Padang Lawas Regency. Child custody rights are the responsibility of the father towards all children including those under the age of twelve. The Padang Lawas community gives child custody rights to the father on the grounds that children are the successors of the lineage or the Patrilineal System. The wife is considered a newcomer after a divorce so she does not have child custody rights, but is still allowed to live with her mother but not forever just to relieve longing. Keywords: Child Custody, Divorce, Padang Lawas, Patrilineal System